2012
DOI: 10.5430/bmr.v1n4p99
|View full text |Cite
|
Sign up to set email alerts
|

Leading Together for Mutual Benefit: Shared Leadership in the Context of Co-operative Banking

Abstract: While also opposing views have been presented, reaching decisions in co-operatives has primarily been considered to be a collective process. Despite this longstanding belief, there is lack of research on the collectivity of leadership processes actually ongoing in co-operative context(s). The paper at hand makes use of shared leadership construct showing that it helps us think of and articulate how leadership manifests in co-operative banks and their co-operative arrangements. The utility of this idea for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The exercise of voice requires leadership capabilities to be widely disseminated through the organisation with the result that leaders emerge and are appointed not just according to formal status but also according to the needs of the situation. In their study of OP-Pohjola Group, a Finnish financial group containing 198 local member co-operative banks, Saila et al (2012) identified the following characteristics by which shared leadership could be recognised: recognised in the quality of interactions; evaluated by how well the problem was solved together; enacted in how all individuals contributed to the process of leadership; understood as a joint effort of interdependent individuals, including high levels of communication; and aimed at mutual benefit and the common good. Finally, the basis of leadership is deliberated authority (Alvesson and Spicer 2013), where coordinative power is legitimated through democratic representation.…”
Section: Source: Yeoman 2015mentioning
confidence: 99%
“…The exercise of voice requires leadership capabilities to be widely disseminated through the organisation with the result that leaders emerge and are appointed not just according to formal status but also according to the needs of the situation. In their study of OP-Pohjola Group, a Finnish financial group containing 198 local member co-operative banks, Saila et al (2012) identified the following characteristics by which shared leadership could be recognised: recognised in the quality of interactions; evaluated by how well the problem was solved together; enacted in how all individuals contributed to the process of leadership; understood as a joint effort of interdependent individuals, including high levels of communication; and aimed at mutual benefit and the common good. Finally, the basis of leadership is deliberated authority (Alvesson and Spicer 2013), where coordinative power is legitimated through democratic representation.…”
Section: Source: Yeoman 2015mentioning
confidence: 99%